Factors Influencing Teacher Performance at SDN 10 Pantaloon Palu - Manoppo, Bella Cahyaningrum; Adda, Harnida Wahyuni; Rossanty, Ni Luh Putu Evvy; Farid, Erwan Writers (Journal of Humanities, Community Service, and Empowerment, 2024)
This Research investigates the impact of work motivation and stress on teacher performance. Through a search using the keywords "motivation," "stress," and "teacher performance" in the period 2020 to 2023, this Research produced 20 relevant articles. The literature review study method is used in the Indonesian context. The research results show that motivation and stress significantly contribute to teacher performance directly. These findings confirm that work motivation and stress are essential in influencing teacher performance. Other factors influencing teacher performance in educational institutions include job satisfaction, teacher compensation, and teacher competency. Therefore, school leadership management, discipline, working conditions, teacher productivity, rewards, and organizational culture can minimize this negative impact. It is hoped that further Research will be more in-depth, especially in exploring the education sector in Indonesia.